The Ethnomathematics of Calculating Auspicious Days in Javanese Society as Mathematics Learning - Aritsya Imswatama; David Setiadi (SEAMEO Regional Centre for QITEP in Mathematics, 2017)
The purpose of this ethnomatematics research is to describe the process of calculating auspicious days for Javanese wedding in Purworejo. This research is a descriptive research with a qualitative approach which used interviews to collect the data. The subject of this research was an individual who implemented the process of calculating auspicious days in Javanese society. The results show that the process of calculating auspicious days for Javanese wedding in Purworejo was an activity that could be possibly used as mathematics learning.